Fitossociologia e composição bromatológica de espécies herbáceas e subarbustivas em áreas de caatinga sob pastejo - Cassuce, Meiry Rodrigues (2012)
The study of physiognomy and floristic caatinga generate diagnostics about the current state of pastures which together with other information potential, allow the drafting of strategies for conservation and sustainable use of remnant vegetation. This study aimed to understand the floristic composition and phytosociological parameters of herbaceous vegetation and undergrowth under different goat grazing pressure in the Caatinga (1) and study the chemical composition of the pool and five species of vegetation are three species of caatinga of herbaceous species and two size subshrubby during the rainy season and dry (2). The study was conducted at the Experimental Station of the Center for Agricultural Science Center - CCA, Federal University of Paraíba - UFPB in St. John Cariri-PB. Geographical coordinates 7 ° 23'30 "south latitude and 36 ° 31'59" west longitude at an altitude of 458m. The survey was conducted from January to December 2011, totaling 50 weeks of observation in three Caatinga areas, and the area I with 3.1 an / ha, the area II with 1.5 an / ha and the area III with 0 an / ha, which were plotted in each area 30 plots of 1 x 1m, totaling 30sqm. Was assessed absolute and relative density, absolute and relative frequency, and similarity, floristic diversity and aggregation of species. In each plot after germination and seedling emergence of three samples of each species were collected and taken to the herbarium Jayme Coelho de Moraes CCA for identification through expert consultations and comparative morphology, using specialized bibliography and analysis of herbarium specimens deposited in the herbarium. The survey density was based on the quantification of the number of individuals of each species. The herbaceous vegetation and undergrowth in the sampled areas was represented by 71 species belonging to 49 genera and 22 families. The herbaceous flora was represented by 43 species and 28 species of flora undergrowth. With respect to the Area III phytosociological parameters as well as areas I and II showed density values relative to higher frequency forAristida adscensionis, then Diodia teres, Cyperus uncinulatus and Evolvulus cressoides in different periods. The analysis of aggregation (IGA) presented the assessment year different behaviors of the spatial distribution of species in the three forest types studied. The Area III had higher floristic diversity than Areas I and II. The most representative families in the areas of caatinga Cariri Paraibano were Fabaceae, Euphorbiaceae, Malvaceae, xv Convolvulaceae, Rubiaceae and Poaceae. The vegetation types in greater conservation stage shows greater floristic diversity. For chemical analyzes were collected composite samples of five leaves and herbaceous subshrubs and another pool of species present in the three study areas which were identified and selected. The average levels of MS plants ranged from 295,55 to 504,47 g/kg for Pool and Sida galheirensis respectively. To the ether extract (EE), the mean values ranged from 20,78 g/kg DM to 53,73 g/kg DM for Aristida adscensionis and Stylosanthes scabra, respectively, significant difference between species. For crude protein (CP) significant difference between the species, with a higher value of CP for Stylosanthes scabra (167,06 g/kg DM) and lowest for Aristida adscensionis (55,35 g/kg DM). DIMS values ranged from 354,78 g/kg DM (Sida galheirensis) to 535,78 g/kg DM (Diodia teres). The NDF value observed for the species Aristida adscensionis (772,54 g/kg DM) was higher when compared with the others. The ADF ranged from 247,25 to 493,25 g / kg DM for the species Sida galheirensis and Diodia teres, respectively. Among the different species and locations, they showed chemical composition varied, with significant effect (P <0,05) for the chemical composition of species within each sampled area. The period of the year influenced the chemical composition of the pool and grass Aristida adscensionis verifying reduce the variables CP, IVDDM and increase in the percentage of MS in the dry season for both the pool and for the grass. The chemical composition of the species indicates that herbaceous and subshrub layer can constitute a good food source for small ruminants that grazed caatinga.